Speech vs. singing: infants choose happier sounds - Corbeil, Marieve; Trehub, Sandra E.; Peretz, Isabelle (Frontiers in Psychology, 2013)
Infants prefer speech to non-vocal sounds and to non-human vocalizations, and they prefer happy-sounding speech to neutral speech. They also exhibit an interest in singing, but there is little knowledge of their relative interest in speech and singing. The present study explored infants’ attention to unfamiliar audio samples of speech and singing. In Experiment 1, infants 4-13 months of age were exposed to happy-sounding infant-directed speech versus hummed lullabies by the same woman. They listened significantly longer to the speech, which had considerably greater acoustic variability and expressiveness, than to the lullabies. In Experiment 2, infants of comparable age who heard the lyrics of a Turkish children’s song spoken versus sung in a joyful/happy manner did not exhibit differential listening. Infants in Experiment 3 heard the happily sung lyrics of the Turkish children’s song versus a version that was spoken in an adult-directed or affectively neutral manner. They listened significantly longer to the sung version. Overall, happy voice quality rather than vocal mode (speech or singing) was the principal contributor to infant attention, regardless of age.